2020
DOI: 10.1101/2020.05.24.096180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computer code comprehension shares neural resources with formal logical inference in the fronto-parietal network

Abstract: Despite the importance of programming to modern society, the cognitive and neural bases of code comprehension are largely unknown. Programming languages might 'recycle' neurocognitive mechanisms originally used for natural languages. Alternatively, comprehension of code could depend on fronto-parietal networks shared with other culturally derived symbol systems, such as formal logic and math. Expert programmers (average 11 years of programming experience) performed code comprehension and memory control tasks w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 83 publications
2
12
0
Order By: Relevance
“…The results of our work align well with the results of another recent study on program comprehension ( Liu et al, 2020 ). Liu et al investigated the neural correlates of program comprehension by contrasting Python code problems with fake code.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of our work align well with the results of another recent study on program comprehension ( Liu et al, 2020 ). Liu et al investigated the neural correlates of program comprehension by contrasting Python code problems with fake code.…”
Section: Discussionsupporting
confidence: 91%
“…However, none of these prior studies sought to explicitly distinguish code comprehension from other programming-related processes, and none of them provide quantitative evaluations of putative shared responses to code and other tasks, such as working memory, math, or language (cf. Liu et al, 2020 ; see Discussion).…”
Section: Introductionmentioning
confidence: 76%
“…In addition, the set of IFG and IPL has been frequently discussed together as a fronto-parietal network and they often show synchronous activity in a wide range of tasks (Watson and Chatterjee, 2012;Ptak et al, 2017). Importantly, a recent fMRI study on programmers suggested an association between program comprehension and fronto-parietal network that was functionally related to formal logical inference (Liu et al, 2020). Our results are consistent with these findings, implying that the fronto-parietal network plays a key role in experts' program comprehension processes.…”
Section: Discussionmentioning
confidence: 99%
“…A network of left-lateralized frontal and temporal brain regions (here referred to as the language network) has been found to respond to written/spoken/signed words and sentences, but not to mental arithmetic, music perception, executive function tasks, action/gesture perception, or computer programming (Amalric & Dehaene, 2019;X. Chen et al, 2021;Fedorenko et al, 2011;Ivanova et al, 2020;Jouravlev et al, 2019;Liu et al, 2020;MacSweeney et al, 2002;Monti et al, 2009Monti et al, , 2012Pritchett et al, 2018). Similarly, investigations of patients with profound disruption of language capacity ( global aphasia) have shown that some of these individuals can solve arithmetic and logic problems, appreciate and create music, and think about others' thoughts in spite of their language impairment (Basso & Capitani, 1985;Luria et al, 1965;Varley et al, 2005;Varley & Siegal, 2000), providing converging evidence that language is subserved by domain-specific cognitive mechanisms.…”
Section: Introductionmentioning
confidence: 99%